Project Success in IT Project Management - Siddiqui, Farhan Ahmed (2010)
The rate of failed and challenged Information Technology (IT) projects is too high according to the CHAOS Studies by the Standish Group and the literature on project management (Standish Group, 2008). The CHAOS Studies define project success as meeting the triple constraints of scope, time, and cost. The criteria for project success need to be agreed by all parties before the start of the project and constantly reviewed as the project progresses. Assessing critical success factors is another way of measuring project success (Dai, 2001). A proposed solution for achieving the project success in IT project management by indentifying the criteria for success and the factor that affect the success criteria to achieving ultimate success.